Modeling phase-transitions using a high-performance, isogeometric analysis framework - Vignal, P.; Dalcin, L.; Collier, N.; Calo, Victor (2014)
In this paper, we present a high-performance framework for solving partial differential equations using Isogeometric Analysis, called PetIGA, and show how it can be used to solve phase-field problems. We specifically chose the Cahn-Hilliard equation, and the phase-field crystal equation as test cases. These two models allow us to highlight some of the main advantages that we have access to while using PetIGA for scientific computing. © The Authors. Published by Elsevier B.V.